2022
DOI: 10.1136/bmj-2021-068882
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-4 inhibitors and gallbladder or biliary disease in type 2 diabetes: systematic review and pairwise and network meta-analysis of randomised controlled trials

Abstract: ObjectiveTo examine the association between dipeptidyl peptidase-4 inhibitors and gallbladder or biliary diseases.DesignSystematic review and pairwise and network meta-analysis.Data sourcesPubMed, EMBASE, Web of Science, and CENTRAL from inception until 31 July 2021.Eligibility criteriaRandomised controlled trials of adult patients with type 2 diabetes who received dipeptidyl peptidase-4 inhibitors, glucagon-like peptide-1 receptor agonists, and sodium-glucose cotransporter-2 inhibitors compared with placebo o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 126 publications
(139 reference statements)
2
8
0
Order By: Relevance
“…A meta-analysis of 76 RCTs has recently found that compared with placebo or active controls, GLP-1RA treatment was associated with an increased risk of gallbladder or biliary diseases (RR, 1.37; 95% CI, 1.23–1.52) [ 64 ]. Similar findings were noted with dipeptidyl peptidase-4 inhibitors in another meta-analysis of 82 RCTs, in which they increased the risk of gallbladder or biliary diseases (OR, 1.22; 95% CI, 1.04–1.43) compared with controls [ 65 ]. For both therapeutic classes, this increased risk of gallbladder or biliary diseases has been thought to be driven by the inhibition of the secretion of cholecystokinin by GLP-1, leading to impaired gallbladder motility and contractility [ 64 , 65 ].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…A meta-analysis of 76 RCTs has recently found that compared with placebo or active controls, GLP-1RA treatment was associated with an increased risk of gallbladder or biliary diseases (RR, 1.37; 95% CI, 1.23–1.52) [ 64 ]. Similar findings were noted with dipeptidyl peptidase-4 inhibitors in another meta-analysis of 82 RCTs, in which they increased the risk of gallbladder or biliary diseases (OR, 1.22; 95% CI, 1.04–1.43) compared with controls [ 65 ]. For both therapeutic classes, this increased risk of gallbladder or biliary diseases has been thought to be driven by the inhibition of the secretion of cholecystokinin by GLP-1, leading to impaired gallbladder motility and contractility [ 64 , 65 ].…”
Section: Introductionsupporting
confidence: 78%
“…Similar findings were noted with dipeptidyl peptidase-4 inhibitors in another meta-analysis of 82 RCTs, in which they increased the risk of gallbladder or biliary diseases (OR, 1.22; 95% CI, 1.04–1.43) compared with controls [ 65 ]. For both therapeutic classes, this increased risk of gallbladder or biliary diseases has been thought to be driven by the inhibition of the secretion of cholecystokinin by GLP-1, leading to impaired gallbladder motility and contractility [ 64 , 65 ]. Additionally, the weight loss effect of GLP-1RAs may lead to an increased risk of gallbladder disorders [ 64 ].…”
Section: Introductionsupporting
confidence: 78%
“…89,90 Similar to many large-scale population-based studies, 31,56,63,[83][84][85][86][91][92][93][94][95][96][97][98] many biases, which cannot be totally excluded, may decrease the reliability and reproducibility of the data analysis. Additionally, DPP-4i may increase the risk of cholecystitis in randomized controlled trials, especially with longer treatment duration, 99 although the population-based cohort study did not support the current use of DPP-4i was associated with an increased risk of bile duct and gallbladder disease compared with current use of at least 2 oral ADA (adjusted HR, 0.99; 95% CI, 0.75-1.32). 100 By contrast, the risk of bile duct and gallbladder disease seemed to be increased in DM treated with GLP-1 receptor analogues currently.…”
Section: Antidiabetic Agents and Bonementioning
confidence: 84%
“…A recent meta-analysis enrolling 82 randomized controlled trials with 104,833 participants showed DPP-4i was significantly associated with an increased risk of the composite of gallbladder or biliary diseases with an odds ratio (OR) of 1.22 (95% CI: 1.04–1.43) compared with placebo or nonincretin drugs. 5 Additionally, compared with sodium-glucose cotransporter-2 inhibitors, DPP-4i also increased the risk of the composite of gallbladder and biliary diseases, as well as cholecystitis. 5 The prevalence and incidence of gallbladder or biliary tract diseases differ between male and female populations.…”
Section: Dear Editormentioning
confidence: 99%
“…5 Additionally, compared with sodium-glucose cotransporter-2 inhibitors, DPP-4i also increased the risk of the composite of gallbladder and biliary diseases, as well as cholecystitis. 5 The prevalence and incidence of gallbladder or biliary tract diseases differ between male and female populations. The male population may have a higher risk of developing gallbladder or biliary tract diseases than the female population.…”
Section: Dear Editormentioning
confidence: 99%